Conductive PHA wound dressing as well as preparation method and application thereof
By preparing PHA-based conductive film dressings, combining conductive carbon nanotubes and anti-inflammatory drugs, the adhesion damage, compatibility and single function of traditional dressings is solved, and multifunctional healing support for chronic wounds is achieved.
Patent Information
- Application Number
- CN202510475214.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2025-08-08
AI Technical Summary
Existing wound dressings are prone to adhesion to the wound surface, causing mechanical damage, poor biocompatibility and easily causing inflammation, and have a single function. They cannot effectively regulate the wound microenvironment, resulting in difficulty in healing of chronic wounds.
PHA polymer is used to dissolve it in a blended manner with conductive carbon nanotubes and anti-inflammatory small molecule drugs. Conductive films are prepared by casting method and laser drilled to form wound dressings with array holes, combining endogenous electric fields to promote cell proliferation and angiogenesis, and anti-inflammatory effects.
It improves the biocompatibility and flexibility of the dressing, reduces the risk of secondary damage during dressing changes, enhances breathability and conductivity, promotes cell migration and wound healing, and reduces the risk of infection.
Smart Images

Figure CN120437353A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a conductive PHA wound dressing, a preparation method thereof, and applications thereof. Background Art
[0002] Chronic skin wounds are caused by specific pathological factors and are unable to achieve anatomical and functional integrity through normal, orderly, and timely repair processes. These wounds are characterized by a prolonged healing period and susceptibility to secondary infection. Their pathological mechanisms are complex and diverse, with common clinical manifestations including venous leg ulcers, arterial ulcers, diabetic foot ulcers, pressure ulcers, and burn wounds. These wounds not only limit patient mobility and increase psychological burden, but are also prone to serious complications such as systemic infection and even amputation. Studies have shown that persistent, excessive inflammation within the chronic wound microenvironment disrupts the molecular regulatory networks underlying tissue repair, particularly inhibiting keratinocyte migration and proliferation, leading to impeded re-epithelialization. Currently, dressing therapy is the primary intervention in clinical practice. However, traditional dressings, such as gauze and sponges, are often made of synthetic fibers or simply processed natural materials and have significant limitations: their limited physical barrier function prevents effective wound moisture regulation; their lack of biocompatibility leads to mechanical damage to newly formed tissue during frequent changes; and, critically, their lack of active regulation of the wound microenvironment makes it difficult to interrupt the inflammatory cascade or promote repair processes such as angiogenesis.
[0003] The inherent bioelectrical activity of living organisms plays a fundamental role in maintaining tissue homeostasis and repairing injuries. The skin, the body's largest electrically active organ, generates an endogenous electric field after trauma through a transepithelial potential difference. This electrical signal can guide epidermal cell migration and promote the orderly arrangement of collagen. Wound exudate is a key carrier of this endogenous electric field, but its excessive accumulation can hinder oxygen exchange and exacerbate the inflammatory response. However, existing dressings passively absorb exudate, making it difficult to achieve dynamic moisture balance and unable to enhance the endogenous electric field effect through electrical property manipulation. This dual deficiency prevents traditional dressings from breaking the vicious cycle of "inflammation-repair imbalance" in chronic wound healing. The development of new dressings that combine intelligent exudate management, electric field coupling synergy, and multiple bioactivities has become an urgent need in the field of regenerative medicine.
[0004] In recent years, biodegradable polymers have provided new insights into wound dressing innovation, with polyhydroxyalkanoate (PHA) materials attracting significant attention due to their excellent biocompatibility and controllable degradation properties. Clinical studies have confirmed that PHA-based dressings can significantly reduce foreign body reactions, and their three-dimensional porous structure facilitates exudate absorption and gas exchange. However, existing products still have significant limitations: functional design focuses primarily on physical barriers and basic moisturizing, lacking systematic integration in key areas such as anti-inflammatory factor delivery, angiogenic activity, and electrical microenvironment regulation. This single function makes it difficult to meet the multi-stage, multi-dimensional dynamic repair needs of chronic wounds, especially for complex wounds with microcirculatory disorders such as diabetic foot ulcers. Therefore, there is a need to develop a wound dressing that simultaneously achieves multiple functions, such as anti-inflammation, connecting endogenous electric fields to promote cell proliferation and angiogenesis, and preventing adhesion to wound tissue, to provide a better solution for chronic wound repair. Summary of the Invention
[0005] The present invention aims to overcome at least one of the deficiencies of the above-mentioned prior art and provide a conductive PHA wound dressing and its preparation method and application, which can be used to solve the problems of existing wound dressings such as easy adhesion to the wound surface causing mechanical damage, poor biocompatibility and easy induction of inflammation, and single function, while achieving multiple functions such as anti-inflammatory, connecting endogenous electric fields to promote cell proliferation and angiogenesis, and preventing adhesion of wound tissue.
[0006] The technical solution adopted by the present invention is to provide a method for preparing a conductive PHA wound dressing, comprising the following steps:
[0007] S1: dissolving PHA polymer, conductive carbon nanotubes, and anti-inflammatory small molecule drugs in an organic solvent to obtain a PHA-containing mixed solution;
[0008] S2: The PHA-containing mixed solution obtained in step S1 is collected by a casting method to obtain a conductive film;
[0009] S3: drying the conductive film obtained in step S2 to remove the organic solvent, and then forming array holes using a laser punching machine to obtain a conductive PHA wound dressing;
[0010] In step S1, the concentration ratio of the PHA polymer, the conductive carbon nanotubes, and the anti-inflammatory small molecule drug is (60-80):(10-15):1.
[0011] In this technical solution, PHA material is blended with conductive carbon nanotubes and anti-inflammatory small molecule drugs and dissolved in an organic solvent, and a wound dressing is prepared by a casting method. This not only simplifies the traditional multi-layer composite process steps and reduces costs, but also improves the uniformity, flexibility and adhesion of the wound dressing to the wound. The drying process is used to completely remove the organic solvent residue, ensuring biosafety. Specifically, the biodegradability, biocompatibility and natural antibacterial properties of PHA itself are utilized to avoid foreign body reactions and are suitable for sensitive wounds. At the same time, the use of PHA-based materials also gives the wound dressing good hydrophobicity, so that it does not have strong adhesion to the wound tissue, reducing the risk of secondary damage caused by wound tissue peeling during dressing changes. Furthermore, by introducing conductive carbon nanotubes, the dressing is given good electrical conductivity. When applied to the wound, it can connect to the endogenous electric field, accelerate cell migration and wound healing. The anti-inflammatory small molecule drug is directly blended in the matrix, which can directly achieve drug sustained release at the wound site, exerting an anti-inflammatory effect, reducing the inflammatory response of the wound, and reducing the risk of infection. Furthermore, array holes are formed on the wound dressing produced by laser punching technology, which enhances the air permeability of the wound dressing while maintaining a certain mechanical strength, facilitates the outflow of exudate, effectively avoids the accumulation of exudate on the wound surface leading to bacterial growth, and prevents the risk of infection; at the same time, the consistency of the array hole structure is ensured by adopting laser precision punching technology, which is compatible with industrial production needs and improves the stability of wound dressing use.
[0012] Furthermore, the concentration ratio of the PHA polymer, conductive carbon nanotubes, and anti-inflammatory small molecule drug used in step S1 is set to (60-80):(10-15):1. In the blended liquid, the use of a high content (60-80%) of PHA material ensures the overall mechanical strength and processability of the conductive film, avoiding breakage during film casting. At the same time, as the main biodegradable material, ensuring that the proportion of PHA material is 60-80% can make the dressing's degradation cycle in the body better match the healing cycle of chronic skin wounds. At the same time, the incorporation ratio of the conductive carbon nanotubes is set to 10-15%, thereby accurately controlling the surface resistivity of the prepared wound dressing to meet the requirements of electrical stimulation therapy while preventing the conductive carbon nanotubes from agglomerating due to excessive incorporation, thereby reducing the performance of the conductive film. Furthermore, the incorporation amount of the anti-inflammatory small molecule drug is set to 1%, and a low drug loading dressing system is adopted to better match the hydrophobicity and degradation rate of the PHA matrix to achieve long-term sustained release and avoid cytotoxicity caused by initial drug burst release.
[0013] Furthermore, the array holes have a pore size of 0.05-1mm and a pore spacing of 0.1-2mm. By optimizing the pore size and evenly arranging the array holes on the wound dressing, the wound dressing is guaranteed to have high air permeability and exudate management capabilities while maintaining its mechanical properties. Specifically, by comprehensively adopting an appropriate array hole diameter and the ratio between the pore spacing and pore size, the wound dressing's air permeability efficiency and mechanical strength are balanced, making it more adaptable to dynamic wound environments.
[0014] Preferably, the array holes have a hole diameter of 0.1-0.2 mm and a hole spacing of 0.2-0.4 mm.
[0015] Preferably, the concentration of the PHA polymer in step S1 is 6 to 8 wt %. By adopting a PHA polymer substrate of appropriate concentration to adapt to the casting process, the film-forming stability during the wound dressing production process is improved, avoiding the conductive film being easily brittle due to too low a concentration or poor leveling due to too high a concentration, thereby ensuring the thickness uniformity of the conductive film; at the same time, by controlling the concentration of the PHA polymer used, the conductive film produced can better combine mechanical support with a controllable degradation rate, matching the healing cycle of chronic skin wounds, and avoiding premature disintegration or long-term foreign matter residue. Furthermore, a continuous phase matrix is provided by a moderate PHA polymer content, thereby promoting the uniformity of the dispersion of carbon nanotubes and the encapsulation performance of drug molecules, ensuring the integrity of the conductive network and the ability to release drugs.
[0016] Furthermore, the PHA polymer described in S1 includes one or more of P4HB, PHB, PHBV, P34HB, and PHBHHx.
[0017] Furthermore, the conductive carbon nanotubes described in step S1 include single-walled carbon nanotubes, multi-walled carbon nanotubes, carboxylated carbon nanotubes, and hydroxylated carbon nanotubes.
[0018] Furthermore, the anti-inflammatory small molecule drug described in step S1 is one or more of mangiferin, curcumin, taurine, baicalin, paeoniflorin, and aloe extract.
[0019] Furthermore, the parameters of the tape casting method in step S2 are: temperature 15-25°C, humidity 60-80%, area / volume ratio 0.5-1 mL / cm 2 , the standing time is 16-24 hours;
[0020] Furthermore, in step S3, the drying temperature is 20-60° C., and the drying time is 6-8 hours.
[0021] Furthermore, the conductive PHA wound dressing prepared after step S3 has a thickness of 0.2 to 0.5 mm. By ensuring that the wound dressing has a certain thickness, the wound area is guaranteed to withstand a certain amount of traction and deformation during exercise, making the wound less likely to rupture, thereby improving the stability and practicality of the wound dressing.
[0022] Another object of the present invention is to provide a conductive PHA wound dressing obtained by the above preparation method.
[0023] Another object of the present invention is to provide use of the conductive PHA wound dressing in wound repair.
[0024] Preferably, the conductive PHA wound dressing can be used in the repair of chronic skin wounds, where the wounds are located on the skin surface, including but not limited to skin wounds caused by lower limb venous ulcers, arterial ulcers, diabetic foot ulcers, pressure sores and burns.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. By dissolving PHA material, conductive carbon nanotubes, and anti-inflammatory small molecule drugs in an organic solvent and then using a casting method, a conductive PHA wound dressing was prepared. This not only simplifies the traditional multi-layer composite process and reduces costs, but also improves the uniformity, flexibility, and adhesion of the wound dressing. Furthermore, a drying process is used to completely remove organic solvent residues, ensuring biosafety.
[0027] Specifically, the biodegradability, biocompatibility and natural antibacterial properties of PHA itself are utilized to avoid foreign body reactions and make it suitable for sensitive wounds. At the same time, the use of PHA-based materials also gives the wound dressing good hydrophobicity, so that it does not have strong adhesion to the wound tissue, reducing the risk of secondary damage caused by wound tissue peeling during dressing changes; further, by introducing conductive carbon nanotubes, the dressing is given good electrical conductivity, which can connect to the endogenous electric field when applied to the wound, accelerate cell migration and wound healing; anti-inflammatory small molecule drugs are directly blended in the matrix, which can achieve sustained drug release directly at the wound, exert anti-inflammatory effects, reduce wound inflammatory reactions, and reduce the risk of infection.
[0028] 2. On the prepared conductive PHA wound dressing, array holes are formed on the wound dressing produced by laser drilling technology, which enhances the air permeability of the wound dressing while maintaining a certain mechanical strength, facilitates the outflow of exudate, effectively avoids the accumulation of exudate on the wound surface leading to bacterial growth, and prevents the risk of infection; at the same time, the consistency of the array hole structure is ensured by the use of laser precision drilling technology, which is compatible with industrial production needs and improves the stability of the wound dressing.
[0029] 3. In the prepared conductive PHA wound dressing, the concentration ratio of the PHA polymer, conductive carbon nanotubes, and anti-inflammatory small molecule drug is set to (60-80):(10-15):1. Specifically, the use of a high-content PHA matrix ensures the overall mechanical strength and processability of the conductive film, preventing breakage during film casting. Furthermore, as the main biodegradable material, maintaining a 60-80% PHA content allows the dressing's in vivo degradation cycle to better match the healing cycle of chronic skin wounds. Furthermore, the incorporation ratio of the conductive carbon nanotubes is set to 10-15%, thereby precisely controlling the surface resistivity of the wound dressing to meet the requirements of electrical stimulation therapy while preventing excessive incorporation of the conductive carbon nanotubes, which would otherwise lead to aggregation and deterioration of the conductive film's performance. Furthermore, the incorporation level of the anti-inflammatory small molecule drug is set to 1%. By adopting a low drug loading dressing system, the hydrophobicity and degradation rate of the PHA matrix are better matched to achieve long-term sustained release, avoiding cytotoxicity caused by initial drug burst release. . BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a physical picture of the PHA-CM wound dressing provided in Example 1 of the present invention;
[0031] Figure 2 This is a conductivity bar graph of the PHA-CM wound dressing provided in Example 1 of the present invention;
[0032] Figure 3 This is a diagram showing an in vitro cell antioxidant experiment of the PHA-CM wound dressing provided in Example 1 of the present invention;
[0033] Figure 4 Biocompatibility and live cell staining of the PHA-CM wound dressing provided in Example 1 of the present invention;
[0034] Figure 5 This is a graph showing the surface optical contact angle measurement of the PHA-CM wound dressing provided in Example 1 of the present invention;
[0035] Figure 6 This is a cold-field scanning electron micrograph of the PHA-CM wound dressing provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present application belongs.
[0037] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof.
[0038] The present invention will now be further described in conjunction with specific examples. The following examples are only intended to explain the present invention but do not limit the present invention. The test samples and test procedures used in the following examples include the following (if the specific experimental conditions are not specified in the examples, they are usually based on conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources).
[0039] Example 1
[0040] This embodiment provides a method for preparing a conductive PHA wound dressing, comprising the following steps:
[0041] S1: dissolving PHA polymer, conductive carbon nanotubes, and anti-inflammatory small molecule drugs in an organic solvent to obtain a PHA-containing mixed solution;
[0042] S2: The PHA-containing mixed solution obtained in step S1 is collected by a casting method to obtain a conductive film;
[0043] S3: Drying the conductive film obtained in step S2 to remove the organic solvent, and then using a laser punching machine to create array holes, wherein the pore size of the array holes is 0.05-1 mm and the pore spacing is 0.1-2 mm, to obtain a conductive PHA wound dressing;
[0044] Specifically, in step S1, the concentration ratio of PHA polymer, conductive carbon nanotubes, and anti-inflammatory small molecule drugs is (60-80):(10-15):1, and the concentration of PHA polymer is 6-8wt%; the PHA polymer adopts one or more of P4HB, PHB, PHBV, P34HB, and PHBHHx; the conductive carbon nanotubes adopt one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carboxylated carbon nanotubes, and hydroxylated carbon nanotubes; the anti-inflammatory small molecule drugs adopt one or more of mangiferin, curcumin, taurine, baicalin, white paeoniflorin, and aloe extract.
[0045] In step S2, when the conductive film is prepared by the casting method, the parameters of the casting method used are: temperature 15-25°C, humidity 60-80%, area / volume ratio 0.5-1 mL / cm 2 , the standing time is 16-24 hours.
[0046] In step S3, the conductive film obtained in step S2 is dried to remove the organic solvent. The drying temperature is 20-60° C. and the drying time is 6-8 hours. The thickness of the wound dressing obtained is 0.2-0.5 mm.
[0047] Example 2
[0048] This embodiment provides a method for preparing a conductive PHA wound dressing, comprising the following steps:
[0049] S1: PHA polymer, conductive carbon nanotubes, and anti-inflammatory small molecule drugs are blended and dissolved in an organic solvent to obtain a PHA-containing mixed solution, wherein the concentrations of the PHA polymer and the conductive carbon nanotubes are 6 wt% and 1 wt%, respectively, and the concentration of the anti-inflammatory small molecule drug is 0.1 wt%.
[0050] Among them, PHA polymer is P4HB, and the finished P4HB product is purchased from Beijing PHAmily Microstructure Factory Biotechnology Co., Ltd.; conductive carbon nanotubes are single-walled carbon nanotubes, and anti-inflammatory small molecule drugs are mangiferin (Mgf), which are purchased from Aladdin Biochemical Technology Co., Ltd.
[0051] S2: The PHA-containing mixed solution obtained in step S1 is used to prepare a conductive film by a casting method:
[0052] 20 mL of the polymer solution was poured into a round glass dish with a diameter of 7.5 cm and allowed to stand in a fume hood at 25° C. and 70% humidity for 18 h.
[0053] S3: The conductive film obtained in step S2 is placed in a vacuum oven at 40°C and dried for 6 hours to remove the organic solvent to obtain a conductive PHA wound dressing; laser array drilling is performed on the obtained conductive PHA wound dressing, and the array holes have a pore diameter of 0.1-0.2 mm and a hole spacing of 1.2-0.4 mm to obtain a conductive PHA / CNT / Mgf wound dressing (PHA-CM) with array holes.
[0054] Comparative Example 1
[0055] This comparative example provides a method for preparing a conductive PHA wound dressing, comprising the following steps:
[0056] S1: PHA polymer, conductive carbon nanotubes, and anti-inflammatory small molecule drugs are blended and dissolved in an organic solvent to obtain a PHA-containing mixed solution, wherein the concentrations of PHA polymer and conductive carbon nanotubes are 6 wt% and 1 wt%, respectively, and the concentration of mangiferin is 0.1 wt%.
[0057] Among them, PHA polymer is P4HB, and the finished P4HB product is purchased from Beijing PHAmily Microstructure Factory Biotechnology Co., Ltd.; conductive carbon nanotubes are single-walled carbon nanotubes, and anti-inflammatory small molecule drugs are mangiferin (Mgf), which are purchased from Aladdin Biochemical Technology Co., Ltd.
[0058] S2: The PHA-containing mixed solution obtained in step S1 is used to prepare a conductive film by a casting method:
[0059] 20 mL of the polymer solution was poured into a round glass dish with a diameter of 7.5 cm and allowed to stand in a fume hood at 25° C. and 70% humidity for 18 h.
[0060] S3: The conductive film obtained in step S2 was placed in a vacuum oven at 40° C. and dried for 6 hours to remove the organic solvent, thereby obtaining a conductive PHA wound dressing.
[0061] In order to better illustrate the technical effects of the present application, the conductive PHA wound dressing with array holes prepared in Example 2 was subjected to surface morphology characterization, conductivity testing, in vitro cell antioxidant analysis, biocompatibility analysis, and optical contact angle analysis.
[0062] Effect Example 1
[0063] In this effect example, the conductive PHA / CNT / Mgf wound dressing (PHA-CM) with array holes obtained in Example 2 and the non-perforated conductive PHA wound dressing obtained in Comparative Example 1 were characterized by macroscopic and microscopic surface morphology using a scanning electron microscope (S-4800, 10.0 kV).
[0064] according to Figure 1 As shown, the conductive PHA-CM wound dressing prepared in Example 2 and the non-perforated conductive PHA wound dressing prepared in Comparative Example 1 both have a double-sided asymmetric structure: one side is relatively smooth and the other side is relatively rough. Specifically, after the conductive PHA-CM wound dressing prepared in Example 2 is perforated by the laser array, the dressing forms a regular matrix of pores with a pore diameter of approximately 0.1-0.2 mm. Such uniformly distributed macropores are conducive to the discharge of exudate, effectively preventing the accumulation of exudate on the wound surface and causing bacterial growth, thereby preventing the risk of infection.
[0065] Secondly, the microscopic surface morphology of the conductive PHA-CM wound dressing prepared in Example 2 after drying was characterized, and the results were as follows: Figure 6 Scanning electron microscopy results show that a large number of carbon nanotubes are dispersed on both sides of the conductive PHA-CM wound dressing, which is beneficial to the surface conductivity.
[0066] Effect Example 2
[0067] This effect example uses a four-probe conductivity tester to measure the conductivity of the conductive PHA-CM wound dressing prepared in Example 2 after drying. The results are as follows: Figure 2 shown.
[0068] according to Figure 2 It can be seen that the electrical conductivity of both the smooth and rough surfaces of the PHA-CM wound dressing can reach above 1 S / cm, indicating that the PHA-CM wound dressing has good electrical conductivity and can therefore better couple the endogenous electric field.
[0069] Effect Example 3
[0070] In this effect example, the conductive PHA-CM wound dressing prepared in Example 2 was subjected to in vitro cellular antioxidant analysis.
[0071] Specifically, the conductive PHA-CM wound dressing was incubated with complete culture medium for 24 hours to obtain an extract; then 100 μL of complete culture medium (negative group), complete culture medium containing 200 μM hydrogen peroxide (positive group), and extract containing 200 μM hydrogen peroxide (experimental group) were co-cultured with L929 mouse fibroblasts for 6 hours. The ROS fluorescent probe DCFH-DA was used to detect the ROS level in the cells, and the cell nuclei were stained with Hoechst. The morphological characteristics of the cells were examined using an inverted fluorescence microscope, and the results were as follows: Figure 3 shown.
[0072] according to Figure 3 Fluorescence images showed that compared with the hydrogen peroxide group, the level of intracellular reactive oxygen species in the experimental group was lower and similar to that in the negative group, indicating that PHA-CM wound dressing has good anti-inflammatory properties.
[0073] Effect Example 4
[0074] This effect example conducts biocompatibility analysis on the conductive PHA-CM wound dressing prepared in Example 2.
[0075] Specifically, the conductive PHA-CM wound dressing was soaked in complete culture medium for 24 hours to obtain an extract. The PHA / PVP / Cur group used the extract, while the control group used complete culture medium. L929 mouse fibroblasts were co-cultured with the extract for 72 hours. The CCK-8 intensity of the extracts was measured using a microplate reader to analyze cytotoxicity. Calcein-AM, a live cell fluorescent dye, was used to analyze cell growth.
[0076] according to Figure 4 It can be seen that after co-culture of the conductive PHA-CM wound dressing with L929 cells for 72 hours, the PHA-CM wound dressing had no obvious toxic effect on the cells compared with the control group, which indicates that the conductive PHA-CM wound dressing has good biocompatibility.
[0077] Effect Example 5
[0078] This effect example performs optical contact angle analysis on the conductive PHA-CM wound dressing prepared in Example 2.
[0079] The surface water contact angles of the smooth and rough surfaces of the conductive PHA-CM wound dressing were measured using an optical contact angle analyzer (DSA 100). Figure 5 As shown in the figure, the surface water contact angles of the smooth and rough surfaces of the conductive PHA-CM wound dressing were 109.5±2.1° and 125.1±2.4°, respectively, which indicates that the conductive PHA-CM wound dressing has good hydrophobicity and low adhesion to the wound tissue.
[0080] Obviously, the above embodiments of the present invention are merely examples for the purpose of clearly illustrating the technical solutions of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the claims of the present invention shall be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a conductive PHA wound dressing, characterized in that: The steps include: S1: dissolving PHA polymer, conductive carbon nanotubes, and anti-inflammatory small molecule drugs in an organic solvent to obtain a PHA mixture; S2: The PHA mixture obtained in step S1 is collected by a casting method to obtain a conductive film; S3: drying the conductive film obtained in step S2 to remove the organic solvent, and then forming array holes using a laser punching machine to obtain a conductive PHA wound dressing; In step S1, the concentration ratio of the PHA polymer, the conductive carbon nanotubes, and the anti-inflammatory small molecule drug is (60-80):(10-15):
1.
2. The preparation method according to claim 1, characterized in that In step S3, the aperture size of the array holes is 0.05-1 mm, and the hole spacing is 0.1-2 mm.
3. The preparation method according to claim 2, characterized in that The concentration of the PHA polymer in step S1 is 6-8 wt%.
4. The preparation method according to any one of claims 1 to 3, characterized in that The PHA polymer described in step S1 includes one or more of P4HB, PHB, PHBV, P34HB or PHBHHx.
5. The preparation method according to any one of claims 1 to 3, characterized in that The conductive carbon nanotubes described in step S1 are one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carboxylated carbon nanotubes, and hydroxylated carbon nanotubes.
6. The preparation method according to any one of claims 1 to 3, characterized in that The anti-inflammatory small molecule drug described in step S1 is one or more of mangiferin, curcumin, taurine, baicalin, paeoniflorin, and aloe extract.
7. The preparation method according to any one of claims 1 to 3, characterized in that The parameters of the casting method in step S2 are: temperature 15-25°C, humidity 60-80%, area / volume ratio 0.5-1 mL / cm 2 .
8. A conductive PHA wound dressing obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the conductive PHA wound dressing according to claim 8 in a dressing for wound repair.
10. The use according to claim 9, characterized in that The wound surface is a chronic skin wound, and the wound surface is located on the skin surface.